The Effectiveness of Online Learning Using Information Search Methods on Learning Outcomes of 5th Grade Science Subjects at Kemala Bhayangkari Elementary School - Rusmiarti Rusmiarti; Hermansyah Hermansyah; Susanti Faipri Selegi (Buana Pendidikan, 2022)
Online learning is learning that uses technology such as electronic devices. In this case, a teacher must have other alternative ways to deliver learning materials in order to arouse students' enthusiasm for learning. The information search method is one of the learning methods that can be used by a teacher in teaching during online learning, namely by giving students the freedom to seek answers or information from any source in accordance with the related material. The purpose of this study was to determine the effectiveness of online learning using the information search method on the learning outcomes of fifth grade science subjects at Kemala Bhayangkari Elementary School. The research subject is the fifth grade of SD Kemala Bhayangkari. This type of research is True Experimental Design in the form of One Group Pretest-Posttest Design. The results showed that after the pretest, treatment, and posttest were carried out in the experimental class, the average value of the pretest on science learning outcomes was 67.29 while the posttest average value of science learning outcomes was 86.66 and the results of the t-test calculation showed that > ​​( 4,967 > 2,201). So it can be stated that it is accepted and rejected, so it can be concluded that online learning using the information search method is effective for the fifth grade science subject at SD Kemala Bhayangkari.